2018
DOI: 10.1136/bmjopen-2017-019243
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of workers at a New Zealand agrochemical plant to assess the effect of dioxin exposure on mortality

Abstract: ObjectivesTo describe how the exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) influenced mortality in a cohort of workers who were exposed more recently, and at lower levels, than other cohorts of trichlorophenol process workers.DesignA cohort study.SettingAn agrochemical plant in New ZealandParticipants1,599 men and women working between 1 January 1969 and 1 November 1988 at a plant producing the herbicide 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) with TCDD as a contaminant. Cumulative TCDD exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Some studies have shown a small increase in the risk of cancer in workers exposed to herbicides contaminated with higher chlorinated dioxins (Kogevinas et al, 1997). However, other studies show that there is no increased risk for all types of cancer at lower levels of exposure to dioxins (McBride et al, 2018). In our study, the 2,4-D formulation is in accordance with the concentration of dioxins assessed as permissible by IARC (IARC, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown a small increase in the risk of cancer in workers exposed to herbicides contaminated with higher chlorinated dioxins (Kogevinas et al, 1997). However, other studies show that there is no increased risk for all types of cancer at lower levels of exposure to dioxins (McBride et al, 2018). In our study, the 2,4-D formulation is in accordance with the concentration of dioxins assessed as permissible by IARC (IARC, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…The standardized NHL mortality ratio was 1.57 (95% CI: 0.32-4.59) in a New Zealand cohort of 1599 workers between 1969 and 1998 in a production factory of 2,4,5-trichlorophenoxyacetic acid contaminated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The authors conclude that these results do not support the carcinogenicity of TCDD at low levels of exposure [23]. The recent meta-analysis of Satta et al did not show a relationship between exposure to ionizing radiation at dose levels generally encountered in the workplace and the occurrence of lymphomas [24].…”
Section: Discussionmentioning
confidence: 88%